Characteristics of geological evolution based on the multifractal singularity theory: A case study of Heyu granite and Mesozoic tectonics - Dong Wenchao; Jiang Zhongfeng; Zhang Peixin; Zhang Yuchan; Liu Leyi (Open Geosciences)
Tectonic movement and magmatic activity are complex geological processes resulting from the interaction of multiple factors. These processes are often characterized by local singularities with nonlinear characteristics. This study drew on the Multifractal Local Singularity theory and took the Heyu granite magmatism and the Mesozoic tectonic evolution of the Xiong’er Mountain as examples to explore singularity characteristics in the process of tectonic evolution and magmatism. The aim was to enhance the understanding of geological evolution and offer new perspectives for studying geological evolution processes. The research showed that during the four stages of the Heyu granite magmatism, the early phase exhibited a low singularity index, weak magmatic activity, and relatively rapid crystallization. In the middle phase, the singularity index and eruption intensity gradually increased, whereas the crystallization rate decreased. The third stage had the highest singularity index and peak eruption intensity, with the lowest crystallization rate. In the final stage, the singularity index decreased, eruption intensity weakened, and crystallization rate increased. In the case of the Mesozoic tectonic evolution of the Xiong’er Mountain, three distinct stages were identified: early-stage compression and warming, mid-stage structural transformation, and late-stage decompression and extension. The singularity characteristics show a progressive increase from the early to the late stages, indicating a gradual intensification of tectonic activity.